2006
DOI: 10.3139/217.0060
|View full text |Cite
|
Sign up to set email alerts
|

New Multicomponent Compatibilization System for Polyolefin/Polystyrene Blends

Abstract: An efficient compatibilization system based on a combination of styrene-butadiene block copolymer (SBS) with ethenepropene random copolymer (EPM) has been developed for polyolefin/polystyrene blends. Model blends of polypropylene and polystyrene have been taken for compatibilization studies. Concentration of combined compatibilizer in all studied blends was 5 or 10 wt. %. The ratio of EPM/SBS in the compatibilizers was varied from 4/1 to 1/4. Tensile impact strength was used as the main criterion of compatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…4(a)]. This type of morphology, called a honeycomb‐like structure, has already been described in PP/PS blends with a PP matrix compatibilized with a commercial triblock SBS3, 43 or poly(styrene‐ block ‐ethene‐ co ‐propene) diblock copolymer 3. With the copolymer content reduced to 2.5 wt %, this morphology is still preserved, but the internal structure of the dispersed particles becomes less developed [Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…4(a)]. This type of morphology, called a honeycomb‐like structure, has already been described in PP/PS blends with a PP matrix compatibilized with a commercial triblock SBS3, 43 or poly(styrene‐ block ‐ethene‐ co ‐propene) diblock copolymer 3. With the copolymer content reduced to 2.5 wt %, this morphology is still preserved, but the internal structure of the dispersed particles becomes less developed [Fig.…”
Section: Resultsmentioning
confidence: 65%
“…In our previous work, we have shown that the combination of an SB block copolymer and an EPM random copolymer can be a more efficient compatibilization system than a neat SB copolymer for polyolefin/PS blends, even though neat EPM does not act as a compatibilizer at all 40–43. Furthermore, it has been proved that this synergic activity is caused by the formation of an EPM/SB double layer at the interface; EPM is located on the polyolefin side and SB is located on the PS side of the interface 43. However, no systematic study of the influence of EPM properties on the compatibilization efficiency of EPM/SB systems has been carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size distribution of PS particles is very broad, and the amount of SB partitions increases with their size. This type of morphology, called a honeycomb‐like structure, has already been described in PP/PS blends with a PP matrix compatibilized with a commercial SBS [3, 56] or poly(styrene‐ block ‐ethene‐ co ‐propene) diblock copolymer [3] and in LDPE/PS blends compatibilized with SB1 and SB4 [28]. However, compression‐molded sample of LDPE/PS having LDPE matrix and compatibilized with SB3 contained simple PS particles [28].…”
Section: Resultsmentioning
confidence: 76%
“…This result can be due to the degradation of the polymers, since the polymeric chains at high temperature and long time can be degraded. [29] This assumption can be checked by analyzing the IR values corresponding to blends processed at 190 8C and different processing time, where the tensile impact is improved, whereas at 210 8C the IR is deteriorated. In addition, the MFI of the polymer after processing increased, indicating that degradation of the polymer has occurred (decreasing of the molecular weight).…”
Section: Processing Conditionsmentioning
confidence: 99%